Abrasive wear of Al2O3-reinforced aluminium-based MMCs - Yilmaz, O; Buytoz, S (Elsevier Sci Ltd, 2001)
The effects of volume fraction, Al2O3 particle size and effects of porosity in the composites on the abrasive wear resistance of compo-casting Al alloy MMCs have been studied for different abrasive conditions. It was seen that porosity in the composites is proportional to particle content. In addition, process variables like the stirring speed, and the position and diameter of the stirrer affect of the porosity content in a way similar to that observed for particle content. In addition, the abrasive wear rates of composites decreased more rapidly with increase in Al2O3 volume fraction in tests performed over 80 grade SiC abrasive paper than in tests conducted over 220 grade SiC abrasive paper. Furthermore, the wear rates decreased with increase in Al2O3 size for the composites containing the same amount of Al2O3. Hence, it is deduced that aluminium alloy composites reinforced with larger Al2O3 particles are more effective against abrasive wear than those reinforced with smaller Al2O3 particles. At the same time the results show that the beneficial effects of hard Al2O3 particles on wear resistance far surpassed that of the sintered porosity in the compocasting metal-matrix composites (MMCs). Nevertheless, the fabrication of composites containing soft particles such as graphite favors a reduction in the friction coefficient. For this reason graphite and copper were used in the matrix in different amounts to detect their effect on wear resistance. Finally, it was seen that wear rate of the composites decreased considerably with graphite additions. (C) 2001 Published by Elsevier Science Ltd. All rights reserved.
Keywords: MMCs; microstructure; compo-casting